Prevalence of psychological distress detected by the PROTECT and PHQ4 questionnaires and subsequent mental health diagnosis. A cross sectional analysis of the outcomes of new arrival health assessments for refugees and asylum seekers in Ireland - Bridget Kiely; James Larkin; Kathryn Mullan; Maitiú ó Tuathail; Emma Coughlan; Debbie Marshall; Margaret Fitzgerald; Fiona O'Reilly (Journal of Migration and Health)
Background: The mental health needs of refugees and asylum seekers are often unmet. Many screening methods for mental health problems in refugees and asylum seekers have been suggested, but the optimal method for identifying those at risk has not been determined. The PROTECT questionnaire and the Patient Health Questionnaire 4 (PHQ4) are two tools currently being used to identify refugees and asylum seekers at risk of mental health problems in Ireland, but there is limited data on the prevalence of positive scores or risk factors for these to inform health service planning. Methods: Cross sectional analysis was conducted of anonymous data of all adult asylum seekers or refugees who completed a PHQ4 and PROTECT questionnaire during their nurse conducted arrival health assessment within a one-year period. Data collected include: gender, age category, marital status, family unit, country of origin, refugee/asylum status, medical conditions, mental health conditions, exposure to violence, PROTECT score, PHQ4 score and outcome of GP mental health review. Statistical analysis was completed using R. Results: 440 people completed a PROTECT and PHQ4 questionnaire. 198 people had a GP review based on either a positive PROTECT or PHQ4 score. Among all participants, 9.1 % (n = 40) were diagnosed with depression, 15.0 % (n = 66) were diagnosed with PTSD, 3.8 % (n = 17) had an adjustment disorder and 3.7 % had anxiety.. There was a positive correlation between PHQ-4 score and PROTECT score, (rs = 0.738, p < .001) although the PROTECT score identified more cases of PTSD and depression. Being female (aOR: 2.47 95 % CI: 1.59–3.86) and country of origin Zimbabwe (aOR: 3.19 95 % CI: 1.56–6.53) was associated with a positive PROTECT score. Country of origin was negatively associated with PROTECT score for Syria (aOR: 0.32 95 % CI: 0.15–0.65). There were similar findings for PHQ4. Conclusions: Rates of depression, anxiety and PTSD were similar to other studies. There was a strong correlation between PHQ4 scores and PROTECT but with PROTECT ultimately identifying more cases of depression and PTSD, suggesting it may be reasonable to use it alone. Whichever screening tool is used, adequate healthcare resources need to be available for further assessment and treatment. Participants from Syria were less likely to have a positive score compared to others and further research is required to understand the reasons for this.